Algılanan Kalite Ve Beyaz Eşya Sektöründeki Uygulamaları - Şevkioğlu, Selen (Fen Bilimleri Enstitüsü, 2012)
Yüksek kaliteli ürünler üretmek yeterli değildir. Kaliteye, tüketici odaklı bakılarak bir üst boyuta geçilmesi gerekmektedir. Ürün ve üretim odaklı bir şirket, Ürünümüz ne kadar kaliteli? diye sorar. Ancak doğru soru Tüketicimize göre ne kadar kaliteliyiz? dir. İlave bir soru daha eklenebilir; Rakiplerimize kıyasla tüketicimize göre ne kadar kaliteliyiz? . Algılanan kalite, bu noktada önemli hale gelmektedir. Bu çalışmanın amacı; • Tüketicilerin mağazalarda ürün satın alma kararı verirken, duyularıyla hangi detayları incelediğini ve bunlara ne kadar önem verdiğini öğrenmek, • Tüketicilerin, algıları yoluyla edindikleri bilgileri mühendislik diline çevirmek, • Hangi ürün özelliklerinin tüketicide yüksek kalite algısı, hangi özelliklerin de düşük kalite algısı yarattığını araştırılmak, nitel ve nicel yöntemlerle tüketicilerden toplanan verileri, ürün tasarım sürecine dahil etmektir. Bu çalışma beyaz eşya kalite algısı üzerine, üç adet uygulama içermektedir. Bu amaçla ilk uygulama olarak; mümkün olduğunca benzer ana özelliklere sahip, farklı markalarda dört adet 84 cm buzdolabı seçilmiş ve Algılanan Kalite Çalışması uygulanmıştır. Hangi ürün özelliklerinin tüketiciye yüksek kalite algısı, hangi özelliklerin de düşük kalite algısı verdiği araştırılmıştır. Aynı zamanda ürünün hangi kısımlarının tüketici için ne derece önemli olduğu incelenmiştir. İnceleme ve değerlendirme, ilgili ürünün ana kısımlarını gösteren ürün ipuçları üzerinden yapılmıştır. Tüketicinin ilk bakışta göremeyeceği detayların da incelenmesini sağlayacak şekilde sorular oluşturulmuştur. İnceleme sonrasında, ürünlere her bir soru üzerinden puan verilmiştir. Çalışmanın sonucunda; çalışmada elde edilen verilerin analizi ile her bir üründe, yüksek ve düşük kalite algısı oluşturan özellikler saptanmıştır. İkinci uygulamada ise; buzdolabı saplarının kalite algısı ve ergonomisi araştırılmıştır. Farklı marka dokuz adet buzdolabı sapının, sap tutma şekilleri gözlemlenerek formları değerlendirilmiş ve ergonomik sap formu ölçüleri, antropometrik ölçüler baz alınarak hesaplanmıştır. Üçüncü uygulama olarak; ankastre fırın arayüz kalite algısı araştırılmıştır. Bu amaçla farklı markalarda dört adet ankastre fırın arayüzleri incelenerek ekranlar, kullanılabilirlik ve panolar, görsellik parametreleri bakımından değerlendirilmiştir. Fırın arayüzlerinde kalite algısını düşüren özellikler ile estetik ve kolay kullanılabilirlik algısı veren özellikler saptanmıştır. Uygulamalarda kullanılan ürünlerin marka ve fiyat bilgileri kapsam dışı tutulmuş, çalışma sonuna kadar katılımcılara bu yönde bilgi verilmemiştir.

Perceived quality can be defined as the customer s perception of the overall quality or superiority of a product with respect to its intended purpose, relative to alternatives. Perceived quality is, first, a perception by customers. It thus differs from actual or objective quality. Objective quality refers to the actual technical excellence of the product that can be verified and measured. Perceived quality cannot necessarily be objectively determined, in part because it is a perception and also because judgements about what is important to customers are involved. Perceived quality differs from satisfaction. A customer can be satisfied because he or she had low expectations about the performance level. High perceived quality is not consistent with low expectations. It is also differs from attitude: A positive attitude could be generated because a product of inferior quality is very inexpensive. Conversely, a person could have a negative attitude toward a high-quality product that is overpriced. This concept is an intangible, overall feeling about a product. However, it usually will be based on underlying dimensions which include characteristics of the products to which the product is attached such as durability and usability. To understand perceived quality, the identification and measurement of the underlying dimensions will be useful, but the perceived quality itself is a summary, global construct. This study gives a review of the notion: definitions, impacts, factors affecting, quality ques and dimensions. Nowadays, as businesses competition becomes greater, the concept is rapidly becoming an important, strategic tool for companies to make a difference of their products. In other words, companies that understand the concept as an important factor for customer decision and that evaluate and continuously improve their products regarding their perception, can better differentiate themselves in the market. But first of all this requires a basic understanding of the perception of the customer during the interaction with a product. What can be noted is that… • …the perceived quality significantly influences the customer’s opinion and, therefore, has an impact on the purchase decision. • …the perception of quality characteristics is a subjective process and happens consciously as well as unconsciously in order to satisfy evident and hidden customer needs. • …due to the scrappiness of information gathered from the customers, perceived quality is often based on the comparison of quality characteristics according to purpose of usage and expectations. This comparison can either be direct or based on experience. • …besides the objective and physical design of the product, the main influence factors are the individually given purpose of usage, aesthetics, environmental influences. It is not efficient to produce high quality products. Product and product-oriented company ask for “ How quality our products are? ”. However, the right question must be How quality our products are according to our customers? dir. An additional question can come as following How quality our products are according to our customers by comparing to our competitors? . Perceived quality becomes important at this point. First of all the company has to find out how itself and its offerings are perceived by the customers. It is essential to identify what the customer is actually buying and which features are most important to him. Only this way it is possible to align the internal focus and resources to the customers expectation. This information is of greater value if it can be compared to the customers‟ perception of competitive offerings. Not only will this reveal relative strengths and weaknesses, it is also a valuable source of ideas for improvement. It is also argued that quality perception is primarily affected by five key variables: 1. Quality cues – either physical characteristics of the product (intrinsic) such as its shape, size, and so on, or features associated with the product (extrinsic) such as its brand name, pricing, etc. 2. Quality attributes – perceived benefits of the product, such as the functions and potential social advantages it offers, either based on actual experience or expert viewpoints. 3. Interactions – the context in which the human engages with the product prior to making quality ratings, including the physical and social environment, and whether it is possible to make comparative judgements. 4. Timing – whether ratings are made pre or post consumption, that is, before or after extensive use of the product. 5. Personal perspective – individual differences, such as level of education, product knowledge, motivation, and so on. The aim of this study; • To get the information about which details they observe by their emotions and how impotant they are, at the point of purchase. • To invert the feedback that is taken by customers perceptions, to engineering. • The final target is to involve following observations to the design; which certain products are giving high quality perception and which are giving low, the data collected by quantitative and qualitative ways. This study also includes three technical applications about the perceived quality of household appliances. For this purpose, as initial application; 4 pieces of different 84-cm refrigerators that are the most possible similars but different branded were chosen and Perceived Quality Study has been applied to them. It was investigated that which parts of the product are important for customer. İnvestigation and evaluation were made on the ques that show the main parts of the product. Questions were prepared to provide to investigate the details that customer can not see at first glance. After review, the products were given points on each question. At the end of the study, the specifications that give high and low quality perception, were detected by the analysis of the data obtained for each product during study. In the second application, ergonomics and quality perception of refrigerator handles were investigated. Shape of nine refrigerators’ handles with different brands were investigated and ergonomic form measurements of handles were calculated on the basis of anthropometric measurements. In the third application, perception of built-in oven interface quality was researched. For this purpose, 4 built-in ovens’ interfaces were chosen and investigated according to “usability” and “visuality”. Characteristics that give perception of esthetics and ease of use, were determined. Brand and price information for products used in applications kept out of the study and the participants were not informed in this direction until the end. Consequently, all producers shouldn t overlook the perceived quality concept and they must make consumer perceptions of quality match actual quality. If they are sure that their products have quality (actual quality). The three following recommendations will be helpful for them to make the perceived product quality match actual quality efficiently. That is: 1. To communicate the quality information continuously. You must communicate the informations about product quality to their customers continuously by using the integrated marketing communications tools such as advertising, public relations, sales promotion, direct marketing, personnal selling etc. 2. Don t talk boastfullly about your products quality. Although your products have the high-level quality, you should not boast your products too much. Often, it will make your customers feel the products can not satisfy them as they highly expected before. Also, the unsatisfaction of your customers will happen. 3. To aware factors affecting quality of products and use them efficiently. You must pay attention to factors affecting quality of products as mentioned earlier. Those factors can affect perceived product quality directly. Certainly, it can easily make your perceived quality change negatively. In addition; one of the great debates in business is whether perceived quality or actual, objective quality is more significant. Since it is clear that objective quality and perceived quality are related, we must be careful not to dismiss one or other approach.
Perceived Quality And Applications On Household Appliances Industry
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Algılanan kalite; kalite ipuçları; algılanan kalite boyutları; ergonomi; kullanılabilirlik; Perceived quality; quality ques; perceived quality dimensions; ergonomics; usability.